2008
DOI: 10.1007/s11548-007-0146-9
|View full text |Cite
|
Sign up to set email alerts
|

New real-time MR image-guided surgical robotic system for minimally invasive precision surgery

Abstract: Object To investigate the usefulness of a newly developed magnetic resonance (MR) image-guided surgical robotic system for minimally invasive laparoscopic surgery. Materials and methods The system consists of MR image guidance [interactive scan control (ISC) imaging, threedimensional (3-D) navigation, and preoperative planning], an MR-compatible operating table, and an MR-compatible master-slave surgical manipulator that can enter the MR gantry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…Masamune et al developed a small robotic system in which a magnetic resonance imaging (MRI) machine controls needle orientation in a narrow gantry space [5]. Hashizume et al developed an MRI-guided surgical robotic system for minimally invasive laparoscopic surgery using a needle insertion manipulator [6]. Krieger et al developed a remotely actuated manipulator for access to prostate tissue under MRI guidance [7].…”
Section: Related Researchmentioning
confidence: 99%
“…Masamune et al developed a small robotic system in which a magnetic resonance imaging (MRI) machine controls needle orientation in a narrow gantry space [5]. Hashizume et al developed an MRI-guided surgical robotic system for minimally invasive laparoscopic surgery using a needle insertion manipulator [6]. Krieger et al developed a remotely actuated manipulator for access to prostate tissue under MRI guidance [7].…”
Section: Related Researchmentioning
confidence: 99%
“…Current research and development of robots and navigation systems for minimally invasive surgery is focused on improving needle insertion and placement [3][4][5]. For example, Bassan et al reported a novel five-degrees-offreedom manipulator for percutaneous needle insertion [6].…”
Section: Related Researchmentioning
confidence: 99%
“…2, a circle in Cartesian coordinates of a gray-level ultrasonic volume can be parameterized with six variables, p = [x 0 , y 0 , z 0 , θ, ϕ, R], where X 0 = (x 0 , y 0 , z 0 ) defines the center of the circle, (θ, ϕ) are the angular parameters describing the unit normal to the circular plane, and R is the radius of the circle. A model for a circle c that employs parameters p can be written as the set of points X = (x, y, z) that lie on the intersection of a sphere and a plane as given by, (1) where…”
Section: Detection Algorithmmentioning
confidence: 99%
“…While there has been recent progress in the realtime use of MRI [1], [2] to guide robotic surgical procedures, such systems are currently not widely available. Concurrently, however, realtime three-dimensional (3D) ultrasonography has become available for clinical use and its availability is increasing owing to its advantages for interventional tasks [3], [4].…”
Section: Introductionmentioning
confidence: 99%